Shape-Controlled Generation of Gold Nanoparticles Assisted by Dual-Molecules: The Development of Hydrogen Peroxide and Oxidase-Based Biosensors. (13th October 2014) - Peng, Chifang; Duan, Xiaohui; Xie, Zhengjun; Liu, Chunli
Abstract : With the assist of dual-molecules, 2-(N-morpholino)ethanesulfonic acid (MES) and sodium citrate, gold nanoparticles (GNPs) with different shapes can be generated in the H2 O2 -mediated reduction of chloroauric acid. This one-pot reaction can be employed to sensitively detect H2 O2, probe substrates or enzymes in oxidase-based reactions as well as prepare branched GNPs controllably. By the "naked eye, " 20  μ M H2 O2, 0.1  μ M glucose, and 0.26 U/mL catalase could be differentiated, respectively. By spectrophotometer, the detected limits of H2 O2, glucose, and catalase were 1.0  μ M, 0.01  μ M, and 0.03 U/mL, respectively, and the detection linear ranges for them were 5.0–400  μ M, 0.01–0.3 mM, and 0.03–0.78 U/mL, respectively. The proposed "dual-molecules assist" strategy probably paves a new way for the fabrication of nanosensors based on the growth of anisotropic metal nanoparticles, and the developed catalase sensor can probably be utilized to fabricate ultrasensitive ELISA methods for various analytes.